2008
DOI: 10.1007/s00424-008-0620-4
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive response of equine intestinal Na+/glucose co-transporter (SGLT1) to an increase in dietary soluble carbohydrate

Abstract: Experimental and epidemiological evidence suggests that consumption of hydrolyzable carbohydrate, hCHO (grain), by horses is an important risk factor for colic, a common cause of equine mortality. It is unknown whether the small intestinal capacity to digest hCHO and/or to absorb monosaccharides is limiting, or even if horses can adapt to increased carbohydrate load. We investigated changes in the brush-border membrane carbohydrate digestive enzymes and glucose absorptive capacity of horse small intestine in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
71
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 46 publications
2
71
0
5
Order By: Relevance
“…These monosaccharides, when accumulated in the enterocytes, exit the cell across the basolateral membrane into the systemic system by another Na + -independent monosaccharide transporter, GLUT2; a bidirectional transporter that can move glucose out or into the cell depending on its concentration gradient (6) . SGLT1 has been shown to be expressed on the brush-border membrane of villus enterocytes in most mammalian species studied (20)(21)(22)(23)(24)(25) . In general, expression levels are higher in jejunum >duodenum > ileum.…”
Section: Intestinal Glucose Transportmentioning
confidence: 99%
“…These monosaccharides, when accumulated in the enterocytes, exit the cell across the basolateral membrane into the systemic system by another Na + -independent monosaccharide transporter, GLUT2; a bidirectional transporter that can move glucose out or into the cell depending on its concentration gradient (6) . SGLT1 has been shown to be expressed on the brush-border membrane of villus enterocytes in most mammalian species studied (20)(21)(22)(23)(24)(25) . In general, expression levels are higher in jejunum >duodenum > ileum.…”
Section: Intestinal Glucose Transportmentioning
confidence: 99%
“…PVDF membranes were incubated for 1 h at room temperature in PBS-TM [PBS containing 0.5% (wt/vol) nonfat dried milk and 0.05% (vol/vol) Tween-20] and then incubated for 1 h with a 1:1,000 dilution of anti-SGLT1 antibody in PBS-TM. The antibody to SGLT1 was raised in rabbits to a synthetic peptide corresponding to amino acids 402-420 (STLFTMDIYTKIRKKASEK), an intracellular loop region of SGLT1 that is conserved among various species (13,18). Immunoreactive bands were detected by incubation for 1 h with affinity-purified horseradish peroxidase-linked anti-rabbit secondary antibody (DAKO) diluted 1:2,000 in PBS-TM, and visualized using an enhanced chemiluminescence system (GE Healthcare).…”
Section: Animals Diets and Tissuesmentioning
confidence: 99%
“…Immunohistochemistry was performed as previously described (13). Frozen fixed tissue was cut into 10-m sections, followed by a 1-h incubation in blocking solution [10% (vol/vol) donkey serum in PBS], at 25°C in a humidifier chamber.…”
Section: Animals Diets and Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, numerous studies, including direct sequencing (5,6), have reported that both the pig and horse possess the sweet taste receptor and these animals are sweet-preferring. Therefore, there is no convincing evidence that any omnivorous or herbivorous mammal has lost the Tas1r2 gene function.…”
mentioning
confidence: 99%